ANALISIS EKONOMI DAN SIFAT FISIKOKIMIA DODOL RUMPUT LAUT - Yuli Wibowo; Bambang Herry Purnomo; Andrew Setiawan Rusdianto (Faculty of Agricultural Technology, University of Jember, 2007)
Seaweed (Eucheuma cottonii) is sea commodities that processed become various food products. Based on this fact, it needs to be explored, especially product with high added value, practice, and was be like by people. Seaweed product that explored in this research is seaweed dodol. The research point is to determine the composition of seaweed dodol with high quality, which are to study the effect of coconut milk and sugar and then economic analysis. The result showed that addition of coconut milk was not give effect on moisture content, Aw, pH and hardness of seaweed dodol. Otherwise, the addition of sugar was significantly affected on Aw, pH and hardness of dodol. Sugar was not significantly effected by moisture. Dodol made by composition of coconut milk 30 % and high sugar (1:3) was a good dodol. The result of economic analysis shown that dodol industry have good prospect. Keywords: Economical analysis, Eucheuma cottoni , formulation, seaweed dodol